(untitled) (KULT_online, 2024)
Politics and time are intertwined. With a theme issue of History and Theory on Chronopolitics, historians Fernando Esposito and Tobias Becker contribute to a better understanding of the relationship between politics and time. On topics ranging from the revolutions of 1989 to the chronopolitics of historiography itself, the articles in this theme issue provide an overview of the possibilities that the concept of chronopolitics offers for the study of politics and time. A valuable read, not just for historians.